Pós-verdade e democracia em uma sociedade hiperconectada - Bertoli, Jessica Maria (2021)
From a Systems Thinking perspective, this study proposes a conceptual model aimed at examining synergies and interdependencies between disinformation, post-truth and democracy in a hyperconnected society. In light of the specialized literature and the analysis of key indicators associated with the use of the Internet and the consumption of online news, a correlational and feedback loops diagram is also proposed. Some of the challenges to democratic stability were identified and discussed, including the tracking of personal data, the formation of filtered bubbles, the emergence of the disinformation industry, the improvement of disinformation techniques, the persuasive use of technologies, the intensification of social tensions, increased skepticism, increased polarization, increased fragmentation of the public sphere, the delegitimization of traditional institutions and the threat to individual privacy and autonomy. In order to contribute to the strengthening of democracy, potential solutions to these challenges were listed and grouped into containment actions, awareness actions and empowerment actions.